2008
DOI: 10.1124/dmd.108.021873
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Human Liver CYP2D6 Expression

Abstract: ABSTRACT:Within the human cytochrome P450 family, specific forms show developmental expression patterns that can affect drug clearance, efficacy, and safety. The objective of this study was to use dextromethorphan O-demethylase activity and quantitative Western blotting to identify CYP2D6 developmental expression patterns in a large (n ‫؍‬ 222) and developmentally diverse set of pediatric liver samples. Immunodetectable levels of CYP2D6 protein determined for selected samples across all age categories showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
82
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(85 citation statements)
references
References 36 publications
2
82
1
Order By: Relevance
“…At birth and shortly thereafter major changes are seen in the activity of liver enzymes (75 ) and transporters (76 ). For example, in the second postpartum week undetectable CYP2D6 expression was observed in 13% of liver samples (77 ). This correlates with the expected 10% of CYP2D6 PMs in the adult population (77 ).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…At birth and shortly thereafter major changes are seen in the activity of liver enzymes (75 ) and transporters (76 ). For example, in the second postpartum week undetectable CYP2D6 expression was observed in 13% of liver samples (77 ). This correlates with the expected 10% of CYP2D6 PMs in the adult population (77 ).…”
Section: Discussionsupporting
confidence: 49%
“…For example, in the second postpartum week undetectable CYP2D6 expression was observed in 13% of liver samples (77 ). This correlates with the expected 10% of CYP2D6 PMs in the adult population (77 ). In addition, based on adult data the OPRM1 118AϾG variant seems promising for application in clinical practice.…”
Section: Discussionmentioning
confidence: 56%
“…The effect of age on enzyme activity has been reported for several major P450s such as CYP2C19, CYP2D6, and CYP3A4 in humans (Ishizawa et al 2005;Stevens 2006;Wauthier et al 2007;Stevens et al 2008). However, the lack of an age effect on these enzymes has also been indicated (Simon et al 2001;Gorski et al 2003;Parkinson et al 2004).…”
Section: Discussionmentioning
confidence: 93%
“…In livers genotyped with at least one functional CYP2D6 allele (i.e., AS $ 1), variability in Cl int appeared to be due to variability in V max , which correlates to CYP2D6 activity. In vitro (Stevens et al, 2008) and longitudinal phenotyping (Blake et al, 2007) studies demonstrated that beyond the first week or two of life, age is not a significant determinant of variability in CYP2D6 activity. However, investigations of the regulation of CYP2D6 gene expression have revealed that a long-range single nucleotide polymorphism can influence the expression of CYP2D6 through enhancement of gene transcription (Wang et al, 2014;Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%